Is monetary policy gender neutral? Evidence from the stock market - Caterina Forti Grazzini; Chi Hyun Kim (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
We use US household survey data from 2001-2017 to investigate whether monetary policy has heterogeneous effects on women's and men's financial portfolio decisions by analyzing their equity investment. On the one hand, monetary policy significantly affects the entry decisions of women, but not of men: after a contractionary shock, the probability of women entering the stock market decreases. On the other hand, monetary policy is gender-neutral for stock market participants: there are no significant differences in exit or in portfolio rebalancing decisions between women and men. Our results suggest that monetary policy does not have a heterogeneous effect on portfolio decisions across genders once women participate in the stock market.
Keywords: E58; J16; G11; 330; Monetary Policy; Gender; Stock Market Participation; Portfolio Choices